Free living soil Nematodes as Ecological Indicators - Bhusal, Daya Ram (Nepalese Journal of Zoology, 2015)
Free living Nematodes communities used as bioindicators of soil health because their composition well correlates with, two critical ecological processes i.e. nitrogen cycling and decomposition in soil . Nematodes indices withstand statistical rigor better than abundances, proportions, or ratios of trophic groups. Nematodes indices respond to a variety of land-management practices, based largely on life history characteristics of families.